α-Amylase and α-Glucosidase Inhibition by Brown Seaweed (Sargassum sp) Extracts - Muhammad Firdaus; Asep Awaludin Prihanto (Research Journal of Life Science, 2014)
Inhibition of intestinal α-amylase and α-glucosidase is an important strategy to control post-prandial hyperglycemia associated with diabetes mellitus. In vitro inhibitory effects of crude extracts of seaweed against α-amylase and α-glucosidase were studied. Crude ethyl acetate extracts of Sargassum aquifolium were the stronger inhibitor to α-amylase and α-glucosidase than others. Furthermore, Sargassum aquifolium ethyl acetate extract significantly suppressed the rise in postprandial glucose level after oral administration of glucose in normal rats. The results of this study suggest that the crude Sargassum aquifolium extract may suppress the rise in postprandial hyperglycemia in vivo in part, through inhibition of alpha amylase and glucosidase.